Colloquial Words in Indonesian Social Media - Fauziah Khairani Lubis; Syamsul Bahri (Randwick International of Social Science Journal, 2022)
Colloquial words are usually found in the caption or status of social media users. It sometimes creates a confuse for the readers or society because it is just understood by certain community. This becomes a unique and an interesting one to be explored. This research aims to investigate more about colloquial words in Indonesian social media captions those are mainly utilized by young people. It was conducted by a descriptive qualitative method using the theory of colloquial speech, Yule (2010). The data was taken from the captions made by social media users, then identified and classified based on its types. Furthermore, the data analysis of colloquial words was done contextually and theoretically. The research findings showed that from 66 colloquial words data, Coinage had become the highest rate percentage in which it is used to show the uniqueness and a trend or style in a social media caption or status. The unique things and new trends are easier to follow by young people, especially in Indonesian social media. Whereas backformation and derivation become the most rarely percentage used in the caption of Indonesian social media.